An Abundance of Fruit Trees: A Garbology of the Artifacts in Animal Crossing: New Leaf - Hansen, Jared (Loading, 2020)
The game series of Animal Crossing is founded on materialism and consumerism, and its mechanics emphasize the economic principles of production, trade, and consumption. And as a social simulator, its gameplay focuses on inventory management, with items and artifacts as rewards for behaviors. Players are urged to customize their town and avatar, by buying and selling clothing, accessories, furniture, and other items. The method of garbology concludes that trash is a valuable resource in revealing the attitudes and motivations of a culture. This article uses garbology to examine the trash left behind by players in ten random towns of Animal Crossing: New Leaf to create a taxonomy of what players valued and disposed of. This study found patterns of production (non-native and “perfect” fruit trees) to maximize monetary gains, and signs of customization through consumption (such as creating a gothic-themed town). The author concludes based on the findings that players of New Leaf are engaged in a culture of economy and thrift, as opposed to conspicuous consumption, per Rathje’s (1984) hypothesis of garbage.